2018
DOI: 10.1002/jrs.5524
|View full text |Cite
|
Sign up to set email alerts
|

The energy of hydrogen bonds in aqueous suspensions of nanodiamonds with different surface functionalization

Abstract: As a result of an experimental study of the Raman scattering valence bands of water in aqueous suspensions of detonation nanodiamonds with different functional surface groups, the energies of hydrogen bonds in suspensions of nanoparticles were calculated for the first time. It is shown that the degree of influence of different functional surface groups of nanodiamonds on hydrogen bonds in aqueous suspension decreases in the series H > polyfunctional surface > OH > COOH. The obtained data are confirmed by model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The exact mechanisms of the formation of the surface PL spectra are still unknown. In many studies, it was shown that the NDs’ PL significantly depends on the functional groups of nanoparticles. However, the surface groups of studied NDs (Figure b) are similar to each other except for the DND CrS air sample that has almost no −CH x groups on the surface. It is for this sample the shape of the PL spectrum differs significantly from those of other NDs.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The exact mechanisms of the formation of the surface PL spectra are still unknown. In many studies, it was shown that the NDs’ PL significantly depends on the functional groups of nanoparticles. However, the surface groups of studied NDs (Figure b) are similar to each other except for the DND CrS air sample that has almost no −CH x groups on the surface. It is for this sample the shape of the PL spectrum differs significantly from those of other NDs.…”
Section: Resultsmentioning
confidence: 79%
“…Photoluminescence (PL) of NDs and CDs is also dependent on the properties of nanoparticles’ surfaces and their immediate environment. For NDs, the depednece of PL on their surface chemistry, on the strength of the environments’ hydrogen bonds, ,, and on interactions with biomolecules , allowed us to distinguish the specific type of ND emission:surface photoluminescence, distinct from the well-studied PL of color centers in the diamond core. Recently, increasingly more authors believe that the source of surface PL of nanodiamonds is the functionalized sp 2 -hybridized carbon on their surfaces. …”
Section: Introductionmentioning
confidence: 99%
“…It is known that when DNDs are suspended in water, the surface carboxyl groups of nanoparticles actively interact with water molecules, as a result of which hydrogen bonds in water are weakened. ,,, This effect can be observed by the changes in characteristics of the stretching band of the Raman scattering of water in DND suspensions.…”
Section: Resultsmentioning
confidence: 99%
“…Nanodiamonds have stable photoluminescence, low toxicity to cells, and a surface that can be functionalized in a certain way, which largely determines the properties of NDs in suspensions and biological systems. The mechanism of ND fluorescence, aside from the one caused by color centers, is not yet fully understood. It was established that the fluorescence of the non-doped NDs has a surface origin, substantially depends on the composition of the surface groups of NDs, and shifts to the red region with an increasing wavelength of exciting light . The latter feature can be caused both by the “red-edge” effect and simply by the presence of various fluorophores on the surface of nanoparticles …”
Section: Introductionmentioning
confidence: 99%
“…Their results show that low‐energy phonons (both optical and acoustical) dominate anharmonic phonon decay in CdS. Laptinskiy et al [ 97 ] used Raman to describe the energy of hydrogen bonds in aqueous suspensions of nanodiamonds with different surface functionalization. Their measured spectra were confirmed by modeling of optimized nanodiamond structures in water clusters and theoretical calculations of the bond parameters in these structures by the density functional theory.…”
Section: Nanomaterialsmentioning
confidence: 99%